Decentralization technology's impact on organizational and societal structure - Calcaterra, Craig James (Walter de Gruyter GmbH, 2021)
Entrepreneurs as well as seasoned business leaders are struggling to innovate and stay ahead of change in the age of decentralization. What separates the companies that get disrupted from the ones that thrive when faced with decentralization? What tactics can be deployed to decentralize large monolithic organizations? Drawing on their experience as researchers and tech entrepreneurs, Professors Calcaterra and Kaal show how to Learn to embrace the change that comes with decentralization Evolve technology, communication, and culture as the business encounters decentralization Use best practices to maintain profitability in the emerging environments of decentralization across industries Combine responsibility with velocity to leverage the advantages of decentralization for the common good The book examines the core infrastructure elements that are needed before the first genuinely decentralized transaction can happen including a legal environment, underwriting, a truly decentralized blockchain that can overcome the blockchain trilemma (decentralization, scaling, security), and efficient governance of blockchains. Decentralization is essential reading for businesses seeking to win in an increasingly decentralized world where adaptation speed is the competitive advantage that matters most.